Research on the Application of Deep Learning In Autonomous Vehicles - Xiong, Sirui (International Journal of Computer Science and Information Technology, 2024)
This paper examines the application of deep learning in autonomous driving vehicles. The rapid development of autonomous driving technology has provided vast possibilities for utilizing deep learning algorithms. Firstly, this paper introduces the technical components and fundamental knowledge of autonomous driving vehicles. It then delves into the basic principles of deep learning in autonomous driving and its specific applications in various aspects, including visual perception, perception and decision-making, and control and execution. Furthermore, challenges faced by deep learning in autonomous driving are discussed, and future development directions are anticipated. Through this study, a better understanding of the current application status and future trends of deep learning technology in the field of autonomous driving can be obtained.